2021
DOI: 10.12669/pjms.37.3.3942
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Chronic Suppurative Otitis Media: An update from a Tertiary Care Hospital in Bangladesh

Abstract: Objectives: Chronic suppurative otitis media is a major cause of acquired hearing impairment, especially in children of developing countries. The study sought to explore the bacteriological profile and their antimicrobial susceptibility among patients of chronic suppurative otitis media from a tertiary care hospital in Bangladesh. Methods: A cross sectional microbiological study was conducted at the Department of Microbiology, Rajshahi Medical College, Bangladesh from January to December 2019. Aural swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…In addition, the isolation rates of Coagulase negative staphylococci , S. pneumoniae and Enterococcus species were 4.4%, 1.8% and 0.4%, respectively. At least one of these bacterial isolates has also been reported in other studies (25,26,29,4042). This study revealed that gram-negative bacterial isolates included E. coli (19.8%), K. pneumoniae (13.2%) , Providencia species (10.7%), P. mirabilis (9.1%), P. vulgaris (9.1%), Acinetobacter species (5.0%), Citrobacter species (3.3%) and K. oxytoca (2.5%).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, the isolation rates of Coagulase negative staphylococci , S. pneumoniae and Enterococcus species were 4.4%, 1.8% and 0.4%, respectively. At least one of these bacterial isolates has also been reported in other studies (25,26,29,4042). This study revealed that gram-negative bacterial isolates included E. coli (19.8%), K. pneumoniae (13.2%) , Providencia species (10.7%), P. mirabilis (9.1%), P. vulgaris (9.1%), Acinetobacter species (5.0%), Citrobacter species (3.3%) and K. oxytoca (2.5%).…”
Section: Discussionsupporting
confidence: 75%
“…As per our studies Gram negative bacteria P aeruginosa was found to be very sensitive to the antibiotic Amikacin in 80% cases and in 100 % cases the resistance was shown to Tazobactum. These studies were also supported by Swayamisidha A et al and Shamala R et al [23][24] .…”
Section: Discussionsupporting
confidence: 71%
“… 27 Our result was slightly higher than reported from Bangladesh (70.8%). 40 The differences in culture positivity rate might be affected by the types of study design and study participants used in the study.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Furthermore, a recently published article from a tertiary care hospital in Bangladesh reported both GNB (55%) and GPB (45%) as etiologies of bacterial ear infection, with S. aureus (37%) and Pseudomonas species (31.5%) were the leading isolates. 40 Different literatures also mentioned S. aureus, P. aeruginosa, Proteus species as the most common isolates from bacterial ear infection. 41–46 Since the natural habitats of most of these bacteria can be skin, environment and soil, ear infection, particularly OE from these isolates 42 , 46 is usually common.…”
Section: Discussionmentioning
confidence: 99%